EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE PAIR AND CHECK DALAM PEMBELAJARAN MATEMATIKA - Desy Novianti; Ika Ratih Sulistiani (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
This article is to obtain results from the application of the Pair and Check type of cooperative learning model in Mathematics subject matter number factorization material in class IV MIN 1 Pasuruan. Researchers use quantitative methods with quasi-type experiment using Pretest and Posttest. The sample used in the study was class IV C students as the experiment class and IV D as the control class which was also a superior class with a total of 25 students and 23 students so that the total sample was 48. Data collection was conducted by holding Pretest and Posttest. The data analysis technique that the research uses is the z test. In the z test results there are significant differences between the control class and the experiment class. At the pretest the average learning outcomes of students in the control class were 47.65 and in the experiment class the average student learning outcomes were 40.8. while the posttest obtained an average of 70.36 in the control class and 81.83 in the experiment class. So that it can be concluded based on the results of these studies that there is influence when applied the type of cooperative learning model Pair and Check in the content of Mathematics study material number factorization in class IV MIN 1 Pasuruan.